The national system of technical vocational education and training in the Philippines: Review and reform ideas - Aniceto C. Orbeta; Emmanuel Esguerra (Philippine Institute for Development Studies (PIDS), 2016)
The role of the National System of Technical Vocational Education and Training (NSTVET) is critical in skill upgrading and development. The rapidly changing technology highlights this need even more. This paper reviews the state of Philippine NSTVET, and identifies and discusses reform ideas. It does so by doing three things, namely, (a) provide a description of the characteristics of an improved NSTVET described in recent sectoral reviews, (b) provide a description of the characteristics and analysis of the performance of the existing Philippine NSTVET, and (c) provide recommendations to improve the system. Among the recommendations provided in the study are: (a) TESDA should focus more on regulation and information provision, (b) greater emphasis on enterprise-based training, (c) make training continuously relevant to industry needs, (d) greater performance orientation in access to public training funds, (e) improved targeting and sufficiency of financial assistance for TVET, (f) ensure quality in community-based training, (g) improve data generation and dissemination, (h) improve capacity for monitoring and evaluation, and (i) improve the image of TVET.
Keywords: J24; M53; 330; Technical Vocational Education and Training; Philippines